2018
DOI: 10.4244/eij-d-18-00099
|View full text |Cite
|
Sign up to set email alerts
|

Invasive strategy and frailty in very elderly patients with acute coronary syndromes

Abstract: An invasive strategy was independently associated with better outcomes in very elderly patients with NSTEACS. This association was different according to frailty status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 21 publications
3
35
2
Order By: Relevance
“…Many studies around the world have reported a high prevalence of frailty in older patients with ACS, from around 30% to 49%. 10,28,30,[43][44][45][46] However, when compared with studies using similar frailty definition, the prevalence of frailty in our study was higher. In the study conducted by Graham et al in 183 patients with ACS aged ≥65 in Canada, the prevalence of frailty was 30.5% using the Edmonton Frailty Scale.…”
Section: Discussioncontrasting
confidence: 78%
“…Many studies around the world have reported a high prevalence of frailty in older patients with ACS, from around 30% to 49%. 10,28,30,[43][44][45][46] However, when compared with studies using similar frailty definition, the prevalence of frailty in our study was higher. In the study conducted by Graham et al in 183 patients with ACS aged ≥65 in Canada, the prevalence of frailty was 30.5% using the Edmonton Frailty Scale.…”
Section: Discussioncontrasting
confidence: 78%
“…Whereas a conservative management was associated with worse outcome in nonfrail patients, this did not occur in frail patients. 31 Similar results were reported by Sanchis et al, 32 who randomized 106 elderly patients with ACS to a routine invasive or a selective invasive strategy. Patients enrolled had to have at least 2 requisites to be considered comorbid patients (peripheral artery disease, cerebral vascular disease, dementia, chronic pulmonary disease, chronic renal failure, or anemia).…”
Section: Discussionsupporting
confidence: 75%
“…Whereas a conservative management was associated with worse outcome in nonfrail patients, this did not occur in frail patients. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The LONGEVO-SCA registry included NSTE-ACS patients >80 years while a geriatric assessment during the first 72 hours of hospitalization 26 was conducted. Of 531 patients, 27.3% were frail, 76.6% of all patients underwent invasive assessment.…”
Section: Discussionmentioning
confidence: 99%